The transition from elite junior athlete to successful senior athlete - implications for athletics high performance programmes - Hollings, S. (Auckland University of Technology, 2013)
National sports federations are under pressure by their government to produce results at all age-group levels in order to achieve visibility, status and funding. Consequently, sports development programmes have focussed on identification and promotion of talent in order to select the best youngsters in the hope they will most likely become the best adults. Transformation of talented youngsters into world-class medallists and finalists is central to the mandate of national sporting organisations in pursuing success in the international arena. The question of how to transition elite junior athletes to senior elite athletes is the key question of this thesis. In an analysis of 130 elite junior track and field athletes, the attrition rate of New Zealand athletes who competed at a World Junior Championships from 1986 - 2006, but did not subsequently represent New Zealand at the senior level, was 74%. However, 32% of New Zealand junior track and field athletes who won medals and made finals at the World Junior Championships became senior global medalists or finalists or won a Commonwealth Games medal. Therefore, if New Zealand wants to produce successful senior athletes, the strategies should include producing more World Junior Championships medalists and finalists and to retain them in the sport. For a national athletics federation to develop a cost effective programme for groups of developing athletes there is the need to establish and implement an effective performance monitoring system that informs the athlete of what is required at each stage of the broad development pathway. A CD-based Performance Progression tool was developed using a mixed linear model of 168,576 competition performances by 1026 male and 991 female world-class athletes across 19 men`s and 19 women`s track and field events. Through the creation of performance trajectories, the developing athlete is able to compare their progression with that achieved by older successful athletes in the same event, when they were at the same age of development. Junior athletes planning a career in athletics would benefit from knowing the probable age of their peak performance and the period over which they can maintain that peak. Knowledge of age at peak performance in athletics could also inform decisions about selection and preparation of athletes for specific events. The current generation of track-and-field athletes should prepare for an age window of ~2.5 y each side of a peaking age of ~23-28 y. Analysis of focus group and interview data of 23 former and current New Zealand elite junior athletes highlighted that the World Junior Championships were perceived by athletes as a point of reference and important in their decisions about continuing to invest their time and resources in athletics. Athletes reported the World Junior Championships were a central part of the pathway to take them to elite senior success and a valuable opportunity to gain experience of world-class international competition. Elite junior athletes who went on to become successful seniors had a substantial commitment to a realistic and clearly defined goal: to be a successful senior international athlete. They also achieved early international success at the senior grade, and perhaps more importantly had a dominant identity as an elite athlete. Conversely, elite junior athletes who tried to balance concurrent life and athletics goals did not succeed as senior athletes. Successfully negotiating the complex and unique transition from elite junior to senior level athletics probably determines the long-term outcome of the athlete. Triangulation of data based on theories of transition and insight into both current quantitative and qualitative information Page | xvii highlighted a number of transition demands that facilitate or thwart a successful transition to the senior level and further identified a number of coping resources for elite junior athlete transition to senior athlete. Stambulova`s (2003) Athlete Career Transition Model was generative in making sense of the data for the sample of participants. The identification of the barriers to the transition and the recognition of internal and external factors that facilitate the coping process enabled the contextualisation of Stambulova`s (2003) Athlete Career Transition Model for the transition of elite junior track and field athletes to successful senior athlete in New Zealand. The contextualisation of the model provides a template to guide policy and practice of the national athletics body to transition their elite junior athletes to successful seniors.